Burnout syndrome in the nursing staff of the critical units of a public hospital in Huánuco, Peru - Pacheco-Venancio, Ángela A. (2022)
Objective.To identify the level of burnout syndrome in the nursing staffof the critical units of a public hospital in Huánuco, Peru. Methods. An observational, prospective and cross-sectional study was developed; a census population of 132 nurses was used, to whom the Maslach burnout inventorywas applied. The chi-square test was used to test hypotheses. Results. 48.5% of the study sample showed a moderate level of burnout syndrome;40.1% showed a severe level; 51.5 % showed a severe level in the emotion alexhaustion dimension; 53 % showed a moderate level in the depersonalization dimension; and 46.2 % were moderate in the lack of personal ful fillment dimension. In general, the burnout syndrome was moderate (p = 0.000). Conclusions. The nursing staff of the critical units perceived a moderate level of burnout syndrome.